KARAKTERISTIK KINERJA CAMPURAN HRS-WC AKIBAT PERUBAHAN BENTUK AGREGAT KASAR - Y.K.O, Halilintar Boma; Erwan, Komala; Kadarini, S. Nurlaily (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
This study aimed to determine how much influence changes in the form of coarse aggregate to the mixture of Hot Rolled Sheet-Wearing Course (HRS-WC) Changes in the form of coarse aggregate in question is additional aggregate mixture coarse flat and oval in the mix HRS-WCserta Measuring the strength characteristics of the mixture HRS -WCdengan Marshall parameters due to changes in the form of coarse aggregates. Mix design carried out in seven stages of manufacture. Making the first stage of the test object using a normal coarse aggregate and composition for stone aggregate 1-1 (18%), 0.5 stone (22%), 0.5 (20%), stone dust (36%), and sand ( 24%), then made a test object as much as 15 pieces, Based on the analysis results of experiments conducted to prove that the use of various forms of coarse aggregate asphalt mixture lonjon flat and the HRS-WC 5%, 10%, and 15% concluded variation aggregate form flat 5% shows the value of the best results of the three variations, From the above conclusions and marshall results can be seen that the greater the percentage of the aggregate number of flat or oval cavity resulted in an increase in the mix and the cavity in the aggregate. The results of the variation form aggregates shows that changes in composition of the filter does not significantly affect the strength characteristics of asphalt mixture are all still meet the standards of the general specifications of public works DGH. From the above conclusions and marshall results can be seen that the greater the percentage of the aggregate number of flat or oval cavity resulted in an increase in the mix and the cavity in the aggregate. The results of the variation form aggregates shows that changes in composition of the filter does not significantly affect the strength characteristics of asphalt mixture are all still meet the standards of the general specifications of public works DGH. From the above conclusions and marshall results can be seen that the greater the percentage of the aggregate number of flat or oval cavity resulted in an increase in the mix and the cavity in the aggregate. The results of the variation form aggregates shows that changes in composition of the filter does not significantly affect the strength characteristics of asphalt mixture are all still meet the standards of the general specifications of public works DGH. Keywords: Filter, Flat Oval, Coarse Aggregate Shape, Marshall Test.